Integration Of 3G Data (Geomagnetic, Gravity And Geology) To Identify Geothermal System Controlled By Geological Structure Of Telomoyo Plateau (Study Case Of Candi Umbul Area) - Boy Utama Bukit (Journal of Petroleum and Geothermal Technology, 2024)
As the technology development, there are more and more new innovations that utilize existing resources to support the energy needs and to fulfill the consumer needs. The energy source that is being discussed at this time is geothermal energy. Geothermal energy sources are considered effective because they are renewable and environmentally friendly when compared to other energies such as fossil energy. In Indonesia itself, geologically, it has a complex series of volcanoes that can be used as a heat source in this new energy innovation. One area that thought to have geothermal potential is the telomoyo mountain area, which is indicated by the manifestation of hot springs on the surface, precisely around Candi Umbul. However, it is necessary to conduct subsurface studies to identify the presence of subsurface structures such as faults or intrusions as heat sources, where this can be overcome using geophysical methods. This research was conducted using the integration of two geophysical methods, namely the geomagnetic method to determine the direction of the fault continuity and the gravity method to determine the regional heat source, and in the other side geological data as a reference for interpretation. From geomagnetic measurements, 163 rock magnetism data were obtained which indicated the existence of a fault continuity with northeast-southwest orientation in the direction of the river flow and cut the manifestation of hot springs. Meanwhile, from 176 gravity topex data, a high complete boguer anomaly value was obtained as an indication of an intrusion in the northeast that was cut by the fault recorded in the geomagnetic data. Based on geophysical data analysis and correlation with geological data from previous studies, it can be assumed that there is a geothermal system in the study area with andesitic intrusion as the heat source, fault structure with northeast-southwest orientation as a weak zone for meteoric water migration, andesite lava as caprock, unit tuff rock as a reservoir and the telomoyo plateau as a recharge area to supply meteoric water from the geothermal system.